The impact of a carbon tax on fossil fuels on the WEF nexus - Ringler, Claudia; Willenbockel, Dirk; Pérez, Nicostrato D.; Rosegrant, Mark W.; Zhu, Tingju (International Food Policy Research Institute, 2018)
The Global Community tries to make progress on 17 Sustainable Development Goals (SDGs) that UN member states adopted in 2015. Key among these are SDG 2: “End hunger, achieve food security and improved nutrition, and promote sustainable agriculture”; SDG 6: “Ensure availability and sustainable management of water and sanitation for all; and SDG 7: “Ensure access to affordable, reliable, sustainable, and modern energy for all”. However, as a result of growing natural resource scarcity, it has become clear that achievements in one of these three SDGs cannot be achieved without impacts— positive or negative—on one or both other SDGs and several other development goals. To understand these interlinkages, reduce negative feedback effects and strengthen positive or synergistic linkages, the concept of the Water-Energy-Food Nexus has been developed. This policy note summarizes the results of a global economic analysis of these interlinkages simulating the introduction of a carbon tax on fossil fuels that was published as Ringler et al (2016).